LEVEL OF AWARENESS OF PSU – BAYAMBANG CAMPUS STUDENTS TOWARDS E – LEARNING TECHNOLOGIES - Sino Cruz, Matthew John F.; Nanlabi, Kim Eric B.; Peoro, Michael Ryan C. (International Journal of Computing Sciences Research, 2019)
Purpose – The study determines and measures the level of awareness of the PSU – Bayambang Campus students towards different e – learning technologies. Method – The researchers employed Quantitative Research Approach. The study determined the profile of the respondents through a demographic questionnaires and the current status of the campus in terms of the ICT Resources and Network Infrastructure. Result – The survey was carried out in order to measure the level of awareness towards different e – learning technologies among students. It was measured in terms of their familiarity to the existing e – learning technologies as well as the known features of these technologies. Although 52.50% of the respondents seem to be familiar to the concepts of e – learning, it is important to take into consideration the extent of their exposure to these technologies and its level of utilization in order to support the learning process. Conclusion – Technology, Support and Users were considered to be important factors that affect the awareness of the students. These technologies can be used to improve the existing learning process if there is enough support for its implementation through policies and provision of the needed resources. Recommendation – In order to improve the awareness of the stakeholders, the researchers recommended that policies on the integration of e – learning technologies must be designed and integrated to the existing learning process. The administration should also provide the needed ICT Resources and Infrastructure in order to support the use of these technologies. They should also provide training for the students and teachers in order to improve their awareness and enable them to use and maximize the benefits of these technologies. Research Implication – The research can serve as a guide for the design of the policies since it provide an overview of the current status of the university in terms of awareness of the students towards these technologies. These technologies can be used to improve the existing learning process of the University and provide a wider avenue for learning and interaction.